10a + 3a - 4a = 9a
a is equal to 1.
4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5
It is the same as: 9a -4a = 5a
9a + 4a = 26 13a = 26 a = 26/13 a = 2
9a squared = 81a^2
so 5a = -20 making a = -4
3a squared plus nine = 19a. 3a to the second power = 9a plus 9 = 19a.
4a4 + 11a3 - 47a3 - 4a + 5 =4a4 - 36a3 - 4a + 5 =4a (a3 - 9a2 - 1) + 5
9a - 8a = a
9a- a number is squared when it is multiplied by itself, so 3a x 3a = 9a.
2a+5a+9a = 16a
(9a + 2)(9a + 2)
a2+9a+20 = (a+4)(a+5) when factored
There is nothing you can do to 9a + 5 without knowing the value of a.
Because of limitations with the question software, some symbols cannot be rendered, so we don't know what operation there is between the 5a and the 4a-1. Assuming a plus sign produces an inconsistent equation. But if we assume a / (slash) for division, we get a quadratic equation that produces some reasonable roots, so here's what I think the question is: Can you solve the following equation for a: 5a/(4a-1) = 9a-4 ? Yes you can! Multiply both sides of the equation by 4a-1. This gives you: 5a = (9a-4)(4a-1) Expand the right side, which gives you 5a = 36a2 -9a -16a + 4 Subtract 5a from both sides and group similar terms: 0 = 36a2 -30a + 4 Now, use the quadratic formula to solve for a(left to the student): a1 = 2/3; a2 = 1/6
-14 + 9a = 389a = 52a = 52/9 or 5.78
9a + 7b *remember to look and understand the letters!*
9a. You take 11 a's: a a a a a a a a a a a and then take away two (minus a, minus a): a a a a a a a a a X X
9a + 3b - 11a - 4b = -2a -b
The simplified expression is -9a -9b.